Aplikasi Magnetic Energy Recovery Switch sebagai Dynamic Voltage Restorer pada motor Induksi - Dwi Dharma Artakusuma; Fransisco Danang Wijaya; Eka Firmansyah (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Renewable energy source likes solar panel and wind turbine have intermittent character from instability power source generated. The instability power source can make dip voltage in power grid which happen in half cycle until few seconds. To stabilize the voltage in power grid from dip voltage, some methods have been developed using power electronics technology like VSI inverter, STATCOM, energy storage, OLTC, and MERS. The power electronic circuits have some advantages, such as small dimensional size and lightweight to keep voltage in power grid. In this paper, the MERS circuit was applied in induction motor which has small full bridge circuit, uncomplexity computation, and low switching frequency, so it needs low end hardware requirement. This paper proposed the use of MERS dc capacitor with 50% value from induction motor resistance. The result shows that MERS has advantage and can keep the voltage in power grid when the voltage below 39% and 15% above rated voltage (220 Vrms) with the recovery time around 0.3 second and keep the dip voltage over 1 second.